An Investigation of the Effect of Entrepreneurial Ecosystem on Startups Success through the Mediating Effect of Self Efficacy, Entrepreneurial Attitude and Entrepreneurial Intention: Applied Study on the Egyptian Startups Entrepreneurs - Amer, Soha; ElGazzar, Sara; Ragheb, Mohamed A.; Hemeida, Fahd A. (The Arab Journal of Administration, 2025)
The study’s objective is to look at the effects of the entrepreneurial ecosystem (access to government policies and regulations, financial support, government programmes and support for assisting new and growing firms, education and training for entrepreneurship, research and development transfer, market openness and barriers to entry as issues for entrepreneurship, commercial and professional infrastructure for entrepreneurs, access to physical infrastructure for entrepreneurship, cultural and social norms) on startup organisation success through the mediating roles of lf-efficacy, , entrepreneurial attitude, and entrepreneurial tention. For this research, the interpretivism philosophy was chosen, and both the inductive approach and mixed analysis were chosen to enable the researcher to fulfill the goals of the ongoing study. Furthermore, the researcher developed interviews and questionnaires as a tool to collect primary data from startup owners and employees in Egypt. Therefore, we found partial support for the impact of entrepreneurial ecosystem dimensions on self-efficacy, entrepreneurial attitude, and entrepreneurial intention. We also found support for the influence of self-efficacy on startup organisational success and performance. The study also confirmed the impact of entrepreneurial attitude and intention on the success and performance of startups. The study concluded that there was partial support for the influence of the entrepreneurial ecosystem on startup organisation success. Finally, the study found partial support for the mediating effect of self-efficacy on the relationship between the factors of the entrepreneurial ecosystem and startup organisational success. Partially supported was the mediating effect of entrepreneurial attitude on the relationship between the factors of the entrepreneurial ecosystem and startup organisational success. The relationship between the entrepreneurial ecosystem and startup organisational success received partial support from the mediating effect of entrepreneurial intention.